2015
DOI: 10.5812/jjm.26590
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Parvovirus B19 Infection in Thalasemic Patients in Isfahan Province, Iran

Abstract: Background:Parvovirus B19, a member of the Erythrovirus genus of Parvoviridae family, causes various clinical illnesses including infectious erythema, arthropathy, hydrops fetalis or congenital anemia, and transient aplastic crises. The B19 virus can be transmitted through respiratory secretions, blood products, and blood transfusion.Objectives:The aim of this study was to detect the B19 virus in thalassemia patients in Isfahan, Iran.Patients and Methods:The prevalence of parvovirus B19 infection was compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
(22 reference statements)
1
3
1
Order By: Relevance
“…Anti-parvovirus B19 seroprevalence was lower in transfused patients than controls (2.4% and 8.5%, respectively). Thus, our findings contrast with other studies where transfusion recipients had significantly higher rates of anti-parvovirus B19 IgG positivity than controls 5 33. We cannot exclude that a few controls consulting the OPD and the allergy and immunology department of the hospital suffered from HEV or parvovirus B19 infection and already had detectable IgG antibodies and/or that patients with thalassemia pay in general more attention to hygiene and disease prevention due to their fragile condition 34.…”
Section: Discussioncontrasting
confidence: 98%
“…Anti-parvovirus B19 seroprevalence was lower in transfused patients than controls (2.4% and 8.5%, respectively). Thus, our findings contrast with other studies where transfusion recipients had significantly higher rates of anti-parvovirus B19 IgG positivity than controls 5 33. We cannot exclude that a few controls consulting the OPD and the allergy and immunology department of the hospital suffered from HEV or parvovirus B19 infection and already had detectable IgG antibodies and/or that patients with thalassemia pay in general more attention to hygiene and disease prevention due to their fragile condition 34.…”
Section: Discussioncontrasting
confidence: 98%
“…The present study revealed a high prevalence of the viruses in the thalassemia major patients 37% (28/75) when compared with study done in Iran by Nikoozad Et al (16) , in this study the rate was 20% (6/30) .the difference may be due to the sample size of the. A small sample size will not provide a precise and reliable estimation of the prevalence and a larger sample size is needed to obtain a higher confidence level.…”
Section: Discussionsupporting
confidence: 43%
“…The objective of the present study was to evaluate the prevalence of acute B19 infections in Iranian patients with beta thalassemia major through the detection of its DNA in their sera by real-time PCR. Nikoozad et al [12] reported a B19 DNA prevalence of 20% in 30 thalassemia major patients in Iran. However, our results show a reduction in prevalence (4%).…”
Section: Discussionmentioning
confidence: 99%
“…Only one epidemiological study on human parvovirus B19 infection in Iranian patients with thalassemia has been reported, in which the prevalence of parvovirus B19 infection was compared between thalassemia major patients and healthy subjects [12]. The lack of sufficient information about the relationship between active B19 infection and thalassemia in Iran underscores the necessity to determine the rate of active B19 infection in thalassemia major patients.…”
Section: Introductionmentioning
confidence: 99%